Stephen J. Ball (ed.) / The RoutledgeFalmer Reader in Sociology of Education, London-New York 2004 (Przegląd Pedagogiczny, 2008)
Recenzja publikacji: Stephen J. Ball (ed.), The RoutledgeFalmer Reader in Sociology of Education, London-New York 2004